Flame Structures of Burner Stabilized Laminar Premixed Flames - Kumar Yadav, Vinod; Ranjan, Prabhat; Yadav, Vijay; Yadav, Omprakash (International Journal of Engineering and Technology, 2018)
In this paper, numerical analysis of flames stabilized over flat-flame burners at 298 K and 1 bar are studied using ANSYS FluentÂ® software. The temperature, velocity and kinetic rate of reaction of methane (CH4)-air mixtures were analyzed by varying the unburnt mixture velocity. The conditions similar to experiments, performed on heat flux method, were created for numerical analysis and the measured results were compared with experimental results. Three-dimensional steady state simulations with one-step chemistry were conducted to predict the curvature effects and flame structure. One-dimensional laminar burning velocity data was also predicted using ANSYS Chemkin -ProÂ® software with GRI Mech. 3.0 reaction mechanism. The experimental and numerical values of laminar burning velocity were 0.358 m/s and 0.361 m/s respectively at 1 bar and 298 K. Through numerical simulation, the thickness of the reaction zone at predicted laminar burning velocity was 0.84 mm and the peak reactions appeared around 0.88 mm above the burner top surface. The maximum predicted temperature was 2250 K which in turn is slightly higher due to the fact that the simulations were conducted using one step chemistry.Â Â Â